The Quality of Life of Patients with Colorectal Cancer and a Stoma in China: A Quantitative Cross-sectional Study. (June 2021) - Liu, Huayun; Zhu, Xiaomei; Yu, Juping; He, Pingping; Shen, Boyong; Tang, Xinhui; Xu, Xianghua; Wei, Di; Chen, Yongyi; Li, Xuying
ABSTRACT: OBJECTIVE: To explore quality of life (QOL) in patients with colorectal cancer and a stoma and factors associated with their QOL. METHODS: A quantitative cross-sectional study was carried out in the stoma and wound care clinic of a cancer hospital in China. Participants were recruited from clinic patients. Investigators collected demographic data and clinical information; QOL was measured using a Chinese version of the stoma-QOL scale. RESULTS: In total, 359 participants took part; 161 (44.8%) had an ileostomy, whereas the others had a colostomy, and about half of the participants (46.5%) had a permanent stoma. The mean age was 57.86 ± 11.92 years. The QOL scores of most participants were poor, with a median value of 49.44. Participants whose stoma was cared for by others had a significantly lower QOL score than those who cared for their own stomas (odds ratio [OR], 1.58; 95% confidence interval [CI], 1.05–2.38; P = .029). Participants with a temporary stoma had a lower QOL score than those with a permanent stoma (OR, 2.08; 95% CI, 1.275–3.40; P = .004). Further, participants with a complication had a lower QOL score than those without (OR, 1.62; 95% CI, 1.07–2.43; P = .022). CONCLUSIONS: These findings suggest a need for well-developed interventions to improve the QOL of these patients. This study provides valuable insights to inform the development of future clinical practice and research in this area in China and beyond. Abstract : Supplemental digital content is available in the text.